Analisis Kecepatan Aliran Pada Penampang Saluran Segi Empat Dan Trapesium Di Saluran Induk Bantimurung Kabupaten Maros - Syarif, Muhammad; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
This study aims to determine the distribution of flow velocity and analyze differences in flow velocity in the rectangular and trapezoidal channels in the Bantimurung main channel, Maros Regency. The research method used is starting from making observations in the field related to the selection of research sites and then collecting data at the selected locations in the field with each sample in each channel. Furthermore, case studies or literature studies from various literature books related to the distribution of flow velocity, and analyzing the comparison of flow rates and how to calculate flow rate. Based on this research, it is obtained that the flow velocity distribution on the trapezoidal channel section and the rectangular channel section shows a large flow velocity value in the center of the channel and decreases when approaching the channel edge. Channel discharge Q in the same channel flow with a different channel cross section, is influenced by the value of the hydraulic radius ( R ) which is different depending on the shape of the channel